OPTIMIZATION AND ENHANCED SACCHARIFICATION OF COIR PITH BY MICROWAVE IRRADIATION USING RESPONSE SURFACE METHODOLOGY - SUBHA, S. LAKSHMI; ISABEL, W.; PRISCILLA, A. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Coir pith is a widespread, low cost, agricultural based readily available lignocellulosic source in India. The main objective of this study is the microwave pretreatment method modified its complex structure and more accessible to the cellulose surface area for enzymatic hydrolysis of microbial communities followed by biogas production. Based on the preliminary studies, an ecofriendly microwave pretreatment method was adopted using variables like microwave intensity (MI) (500-800W), irradiation time (IT) (5-15min) and a solid, liquid ratio(S:L) (3 – 5%) were selected and optimized using central composite design, a subset of response surface methodology. The maximum cellulose saccharification (CS) and hemicellulose saccharification (HS) was observed as 42.17% and 15.02% respectively. To consider the numerical optimization, the desirability value, cost and energy efficiency, the reducing sugar yield of cellulose and hemicellulose saccharification was 43.78 and 16.9% respectively, which is higher than the observed value. The optimal condition for the maximum CS and HS was MI of 690, IT of 12.5, and S:L of 3.5. The chemical analysis of pretreated samples further confirmed that the microwave irradiation could disrupt the complex structure and increase the digestibility of coir pith. These pretreated samples were used as a sole carbon source for future biofuel production.